The President's Lawyer - Robbins, Lawrence (Lawyer) (Thorndike, Maine : Center Point Large Print, 2025)
"After a long career as one of DCs most powerful litigators, Rob Jacobson is faced with the case of a lifetime: the former President of the United States--his childhood best friend--has been accused of murdering his mistress. Rob knows hes the only one who can prove his friends innocence, but he is soon overwhelmed as he attempts to devise a strategy to defend an authoritative man with a taste for infidelity, serious anger issues, and unconventional sexual appetites. As the high-profile case unfurls, the troubled, intertwining pasts of the two men complicate Robs efforts and soon, doubts begin to grow in his head. Could his oldest friend truly be capable of murder or is something even darker at play?"--
Keywords: Ex-presidents -- United States; Fiction; Adultery -- Fiction; Trials (Murder) -- Fiction; Criminal defense lawyers -- Fiction; Washington (D.C.) -- Fiction; Thrillers (Fiction); Legal fiction (Literature); Detective and mystery fiction; Large print books